Using 3D direct manipulation for real-time structural design exploration. Issue 1 (2nd January 2018) - Åkesson, D.; Mueller, Caitlin
ABSTRACT: Impact of decisions in the design process is initially high and declines as the design matures. However, few computational tools are available for the early design phase, thus an opportunity exists to create such tools. New technology opens up new possibilities to create new and novel computational tools. In this work an existing application is adapted for a new novel 3D input device that is named the Leap Motion controller. The controller allows the user to interact with 3D objects on the screen by using fingers and hands. The of result of this work is a conceptual design application which enables very direct manipulation of 3D objects on the screen, which has not before been achieved for this type of application in 3D. An improved human-computer interaction can potentially improve the users understanding of the structural behavior of a model, cognitive engagement in the design task, and encourage further design exploration. Three different cases are implemented which aims to enable the user to explore different design options with emphasis on geometrical form, as this has the greatest potential to improve the structural performance. The case studies demonstrate new potential for building engineering intuition and improving design space exploration through very direct manipulation in 3D. GRAPHICAL ABSTRACT: